Kajian Fonetik: Persamaan dan Perbedaan Arti Kata Bahasa Jawa dan Sunda dalam Bahasa Indonesia - Hisam Alimahmudi; Irwan Siagian (LITERATUS, 2022)
This study aims to examine the phonetic elements in the similarity of words in Javanese and Sundanese. This research is a qualitative descriptive study. The data collection technique used observational interviews with two sources and the data recorded for analysis. The theory used by the researcher is auditory phonetic theory, where the sense of hearing (ears) used to learn something. Two speakers were Tariq Ibra as a single speaker (Java) and Silpia Maulida as a double speaker (Sunda). The data used is the similarity of words in Javanese and Sundanese from both sources. The results of the data analysis concluded that there are seven similar words in Javanese and Sundanese, including g?lis, ag?ng, p?p?k or p?p?g, bade kudu, edan, and mudun. The similarities of the phonetic aspects of the word equation are sound variations (allophones), segmental sounds, and changes in phoneme sounds (neutralization). And the difference in sound from the word equation is the articulation, namely retroflex consonants and lamino-alveolar consonants.